ANALISIS EFEKTIVITAS PENERAPAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN (UUPK) DALAM TRANSAKSI E-COMMERCE DI INDONESIA - Rassya Saputra, Ananda Fadil; Shafwa, Aqila Judya; Umam, Rohmatul (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study looks at how well indonesian e-commerce transactions are handled by the Consumer Protection Law (UUPK) No. 8/1999. The study’s findings, conducted using a normative-empirical qualitative approach, show that the UUPK has not beenoptimal in addressing digital challenges such as low consumer awareness, poor understanding of the UMKM law, long dispute mechanisms (45 days), and misalignment of regulations with technological advancements. Trends in complaints related to fraud, late delivery, and product non-conformity are confirmed by BPKN data (2017-2024). The comparative study with the EU ODR for 15 days suggestedupdates to the UUPK, legal education, a digital dispute system, and proportional sanctions. These steps should help to increase consumer safety and encourage the steady expansion of the digital economy.Keywords: E-commerce, UUPK, Consumer protection, dispute resolution, UMKM